2006
DOI: 10.1007/s00192-006-0143-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diastasis recti abdominis in a urogynecological patient population

Abstract: A urogynecologist's examination typically includes assessment of the abdominal musculature, including the determination of whether a diastasis recti abdominis (DRA) is present. The purposes of the current study were to examine the (1) prevalence of DRA in a urogynecological population, (2) differences in select characteristics of patients with and without DRA, and (3) relationship of DRA to support-related pelvic floor dysfunction diagnoses. A retrospective chart review was conducted by an independent examiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
178
7
29

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(222 citation statements)
references
References 33 publications
(44 reference statements)
8
178
7
29
Order By: Relevance
“…The cut-off value for normal IRD proposed by Beer et al (2009) was set for nulliparous women, and may be considered narrow for women during pregnancy and in the postpartum period. However, our prevalence of DRA of 39% is within the range of other prevalence studies (Bursch 1987;Boissonnault and Blaschak 1988;Spitznagle et al 2007). Published case reports indicate a partial resolution of the DRA at 4 weeks (Hsia and Jones 2000) and 8 weeks postpartum (Boissonnault and Blaschak 1988), which confers with the results of our study, where the prevalence of DRA decreased from 100% during pregnancy to 52.4% at 4-6 weeks after childbirth.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The cut-off value for normal IRD proposed by Beer et al (2009) was set for nulliparous women, and may be considered narrow for women during pregnancy and in the postpartum period. However, our prevalence of DRA of 39% is within the range of other prevalence studies (Bursch 1987;Boissonnault and Blaschak 1988;Spitznagle et al 2007). Published case reports indicate a partial resolution of the DRA at 4 weeks (Hsia and Jones 2000) and 8 weeks postpartum (Boissonnault and Blaschak 1988), which confers with the results of our study, where the prevalence of DRA decreased from 100% during pregnancy to 52.4% at 4-6 weeks after childbirth.…”
Section: Discussionsupporting
confidence: 72%
“…Criteria and cut off point for the diagnosis of DRA vary in the literature (Bursch 1987;Boissonnault and Blaschak 1988;Ranney 1990;Gilleard and Brown 1996;Rath et al 1996;Candido et al 2005;Spitznagle et al 2007;Beer et al 2009;Akram and Matzen 2014), and to date there is no international consensus on the measurement location. In a cadaver study , Rath et al (1996) defined a widening of the IRD more than 10 mm above the umbilicus, 27 mm at the level of the umbilicus and 9 mm below the umbilicus, as pathological DRA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During pregnancy the Linea Alba reduces the resistance to tension and the two bellies of the rectus abdominis (RA) curve round the abdominal wall, increasing the midline separation of the two RA muscles along the Linea Alba (Boissonnault and Blaschak, 1988;Fast et al, 1990;Gilleard and Brown, 1996). This gap, the Inter Rectus Distance (IRD) is often referred as diastasis recti abdominis (DRA) (Noble, 1995;Spitznagle et al, 2007;Coldron et al, 2008). Studies have found that an increased DRA may affect between 30% and 70% of women during pregnancy (Boissonnault and Blaschak, 1988), and that it may remain separated in the immediate postpartum in 34.9% (Boissonnault and Blaschak, 1988) to 60% of women (Bursch, 1987;Boissonnault and Blaschak, 1988;Boxer and Jones, 1997).…”
Section: Introductionmentioning
confidence: 99%